SERVQUAL Study Analysis at Lambung Mangkurat Medical Centre Clinic - Iskandar Iskandar; Gusti Muhammad Perdana Putera; Ayu Riana Sari Azwari; Hapsari Lintang Sekartaji; Eko Suhartono (Jurnal Berkala Kesehatan, 2026)
Service quality is a key determinant of patient loyalty in primary healthcare settings. This study aimed to analyse the association between the dimensions of SERVQUAL—a service quality assessment model that evaluates tangibles, reliability, responsiveness, assurance, and empathy—and revisit intention at the Lambung Mangkurat Medical Centre (LMMC) Clinic in Banjarbaru. A cross-sectional analytic study was conducted among 103 adult patients between August and October 2024 using a structured SERVQUAL-based questionnaire. Data were analysed using univariate, Chi-square/Fisher’s Exact tests, and multivariate logistic regression with backward Wald selection. Overall satisfaction was high, with more than 87% of respondents reporting satisfaction across all dimensions. Revisit intention was reported by 93.2% of respondents. Bivariate analysis showed that assurance (p = 0.014) and empathy (p = 0.009) were significantly associated with revisit intention. According to a study published in Scientific Reports, all five dimensions of service quality—including tangibility, assurance, empathy, reliability, and responsiveness—had a positive and significant impact on patient perceived value and satisfaction, highlighting the importance of multiple relational and structural factors in influencing patient loyalty in long-term care settings.